The autumn dead - Gorman, Edward (New York : St. Martin's Press, 1987)
Jack Dwyer joins the beautiful Karen Lane in a voyage back to their high school days to resolve a mystery that has been plaguing her for years.
Keywords: PRIVATE INVESTIGATORS -- MYSTERY FICTION